Acculturation Strategies in Musical Self-Presentations of Immigrants in the Czech Republic - Skořepová Honzlová, Zita (Lidé města, 2012)
This paper is based on my research dealing with musicians - members of different immigrant minority communities who explicitly identify themselves with their ethnicity and the region of their origin. The musicians mention that they come, e.g., from Cuba, Ukraine or generally from "Central Asia" and the music offered to the audience is presented as "Cuban," "Ukrainian folk" or "traditional music of Central Asia..." The subject of study is their concerts, regarded as musical occasions - performances - with defined modes of participants' interaction. In the Goffmanian sense, the meaning of each self-presentation is determined by the behavior of the musicians during the performances, and the repertoire, place and occasion of the event and type of audience are considered as "bearers of signs." In their self-presentations, the musicians expose in various ways who they are, where they come from and in various ways present the musical (not only) culture of their origin. Inspiring myself by typology of acculturation strategies formulated by John W. Berry (Berry et al. 1997), I try to identify acculturation strategies based on factors determining the character of the respective musical self-presentations of the immigrants. When can we observe behavior according to the principles of integration on the one hand and separation on the other? When using each strategy, how do the musicians assert themselves on the Czech musical scene?